Aturan Batasan Wajar Pembuatan Akta Notaris Beserta Akibat Hukumnya - Marchananda Diva Engracia; Budi Santoso (Notarius, 2023)
AbstractThrough the Regulation of the Central Honorary Council of the Indonesian Notary Association Number 1 of 2017, a notary is given a reasonable limit to make a deed, but even though it has been regulated, there are still notaries who make a deed outside the normal limits. From this background, the writer draws two problems, namely how to regulate the restrictions on the making of a notary deed and the legal consequences of the limitation of making a notarial deed. In this study, the author uses the normative type by focusing on literature review that uses primary legal materials, namely Law no. 2 of 2014 concerning Amendments to Law No. 30 of 2004 concerning the Position of a Notary and Regulation of the Honorary Council of the Indonesian Notary Association Number 1 of 2017. Through rule Number 1 of 2017 it is stated that notaries are limited to making ten deeds per day, then through the regulation on this limit, separate legal consequences arise, which can be in the form of sanctions. for the notary who violates, the sanctions imposed can range from a warning to more severe sanctions. Keywords: rules; limitations; notary deed; legal consequencesAbstrakMelalui Peraturan Dewan Kehormatan Pusat Ikatan Notaris Indonesia Nomor 1 Tahun 2017, notaris di berikan batasan wajar untuk membuat sebuah akta, namun meski telah diatur masih ada notaris yang membuat akta diluar batas kewajaran. Dari latar belakang tersebut penulis menarik dua permasalahan yaitu bagaimanakah pengaturan pembatasan pembuatan akta notaris serta akibat hukum pembatasan pembuatan akta notaris. Dalam penelitian ini penulis menggunakan jenis normatif dengan memfokuskan pada kajian kepustakaan yang menggunakan bahan hukum primer yaitu Undang-Undang No. 2 tahun 2014 tentang Perubahan Atas Undang-Undang No. 30 tahun 2004 tentang Jabatan Notaris dan Peraturan Dewan Kehormatan Pusat Ikatan Notaris Indonesia Nomor 1 Tahun 2017. Melalui aturan Nomor 1 Tahun 2017 disebutkan bahwa notaris dibatasi untuk membuat sepuluh akta perhari, lalu melalui pengaturan tentang batasan ini, muncul akibat hukum tersendiri yaitu dapat berupa sanksi bagi sang notaris yang melanggar, sanksi yang dikenakan dapat berupa teguran hingga sanksi yang lebih berat.Kata kunci: aturan; batasan; akta notaris; akibat hukum